A study to access the prevalence and drivers of COVID-19 vaccine hesitancy in Indian population including health care professional and dental students - A cross-sectional survey - Manisha Saxena; Neel Kant Patil; Mohit Sareen; Manoj Meena; Nitesh Tyagi; Mridula Tak (Wolters Kluwer Medknow Publications, 2022)
Background: The acceptance and availability of effective vaccines are crucial for the success of vaccination programs. Medical doctors and students are the epitome of shaping the public interest in vaccines. Aim: To evaluate the general public's attitudes, including dental students and health care professionals, at the national level towards COVID-19 vaccines and explore the potential drivers for students' acceptance levels. Methods: A national-level cross-sectional study was carried out in May-June 2021 using an online questionnaire. The sample was categorized based on age, gender, academic level, and location. The dependent variable was the willingness to take the COVID-19 vaccine. The independent variables included demographic characteristics, COVID-19-related experience, and the drivers of the COVID-19 vaccine-related attitude suggested by the WHO SAGE. Results: The number of people who answered the questionnaire was 1271. The males accounted for 38.9%, and females were 61.1%. The age group, 18-45 years with 14.7%, has the highest percentage of people who have not taken vaccination. In context to gender, 13.5% of males and 13.1% of females have not taken vaccination. The percentage of vaccination hesitancy is highest in rural areas with 19.5%. The health care professionals were vaccinated with the highest percentage of 89.8%. Conclusion: The vaccination acceptance level of the population for COVID-19 vaccines was good, approximately 63%, and their worrisome level of vaccine hesitancy 27% was governed by demographic, social, and economic factors. The media and social media, public figures, insufficient knowledge about vaccines, and mistrust of governments and the pharmaceutical industry were major hurdles to vaccination.